MURAL SEBAGAI MEDIA KRITIK MASYARAKAT TERHADAP KEBIJAKAN POLITIK PEMERINTAH (Studi Kasus Kota Denpasar) - Wijaya, Cokorda Gde Ananta; Noak, Piers Andreas; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika; Vol 1 No 2 (2022): Jurnal Ilmu Politik, 2022)
This study aims to find out how murals are a medium for public criticism of the policies made by the Denpasar City government and how the Denpasar City government responds to murals as a critical medium. So far, murals are still considered as a form of public protest whose voices cannot be heard by state officials. Therefore, by making murals in strategic areas, mural creators hope that their views on politics can become a public awareness. Thus, the mural object can give attention to the political views made by the mural creator. This research uses a qualitative descriptive research type. The researcher uses this type of associative research with the reason that this research studies the influence or relationship of a state's responsiveness to phenomena that develop in society.